Discutindo a atuação do professor interlocutor de libras a partir de um grupo de formação - Caetano, Priscila Fracasso (2014)
In the mid-1990s, Brazil becomes a signatory to documents assume Inclusive Education as a fundamental task for any country. The deaf education from the perspective of inclusive education, bilingual education and advocates regarding the involvement of different professionals. Among them is given the emphasis on the role of Teacher Interlocutor of Libras (PI). The PI is one of the recent positions that compose the staff of the state of São Paulo Public Schools. Is predicted that he works at schools from state schools who present deaf or hard of hearing students regularly enrolled, with the task of conducting the dialogue between teachers and students with deafness and / or hearing impairment. This study aims to analyze a strategy of continuing education for teachers interlocutors. Three PIs working in state schools in a midsize city of São Paulo participated in this research. The participants comprised a group of training who proposed hold discussions and reflections on the activities of PIs, based on theoretical studies and exchanges of experience. Training group meetings occurred weekly with an average duration of two hours each, totaling ten meetings. Data collected during the training group (open questionnaire, script analysis of the filming of the group, script analysis of the filming of the action of PI and training group transcripts) were discussed in three areas of analysis: 1) The role / function of PI in the classroom and school; 2) Challenges, possibilities and limits of action of PI; and 3) the training group as a space for dialogue / mediation among participants. Analysis of the sequences revealed the need for an area of continuing education among PIs in order to facilitate discussion and reflection on practice. The testimonies of PIs indicate the precariousness of education for deaf students in the reality experienced by the PIs and PRs, since there is not a guideline or a direction work, or even targets set to be followed. This shortcoming of goals and guidelines causes confusion among the doings of each professional. The solutions remain palliative, work is carried out without tenders or purpose, and there is not a policy to bilingual inclusion for the deaf. We therefore conclude that a commitment to quality education for the deaf student becomes practically impossible in the absence of Pedagogical Political support and an effective project that embases and pay attention in fact to the practice of principles of governing a bilingual education for the deaf in school.